Development of Test Instruments Utilizing Multiple Representations for Enhancing Understanding of Motion Kinematics - Dijen, Hildegardis; Hidayati, Hidayati; Hasanah, Daimul (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2024)
Problem-solving in physics remains low due to the limited use of varied or multi-representation test instruments. This study aims to develop a multi-representation-based test instrument on kinematic motion and describe the results of the logical validity and empirical trials of the developed multi-representation-based test instrument for kinematic motion. This research follows a Research and Development (R&D) approach, using stages synthesized from various expert opinions, ranging from needs analysis to test assembly. The research instrument consists of a multi-representation-based test consisting of 30 questions. The data were analyzed using ANATES after being reviewed by three experts. The results indicate that 30 test items were successfully developed, with an average logical validity score of 0.63, demonstrating that the test instrument is valid and feasible for use. Based on statistical analysis, including item validity, difficulty level, discrimination index, and reliability, the empirical validity results show that 11 test items are suitable for use.